Penerapan Ekowisata Pada Perancangan Hotel Resort Bintang Tiga di Pacet - Vicky Alyah; Desrina Ratriningsih (Universitas Sebelas Maret Surakarta, 2020)
Pacet is one of the natural attractions in Mojokerto Regency, East Java. According to the Mojokerto Regency Spatial Plan for 2012-2032, the area of Pacet is a prioritized area for tourism development. Most of tourist areas in Mojokerto, especially in Pacet, have an increase of 30% -70% of visitors since 2015, one of which is Padusan Pacet Tourism Wana. However, it is unfortunate that the increasing number of tourists is not followed by the development of tourist accommodation. Based on the natural potential of Pacet with a cool and pollution-free atmosphere, the application of the Ecotourism concept to Resort Hotel buildings is expected to benefit the surrounding environment in Pacet. The application of Ecotourism to the design of Resort Hotels will be focused on the natural potential of Pacet (Natural Area Focus). In addition, in the future, there will also be land conservation and plants to preserve the natural ecosystem of Padusan (Contribution To Conservation). This concept incorporates local cultural elements of Pacet (Cultural Respect) in Mojokerto District to attract tourists to stay at Resort Hotels in Pacet.